Microstructures and Elemental Distribution of Magnetic Field Pre-Treated Fluted Pumpkin Leaf - Odewole Michael Mayokun; Olalusi Ayoola Patrick; Oyerinde Ajiboye Solomon; Omoba Olufunmilayo Sade (Acta Technologica Agriculturae, 2020)
There is a scarcity of studies on the use of magnetic field for food pretreatment, especially in relation to a knowledge on the pretreatment at the level of microstructures and elemental distribution of food. Therefore, the effect of magnetic field pretreatment on the microstructures and elemental distribution (Na, K, Ca, Mg and Fe) of fluted pumpkin leaf was studied. Three types of magnetic field (static, pulse and alternating) in combination with varying magnetic field strength (5–30 mT) and pretreatment time (5–25 min) were used as variable factors. Fresh (untreated) and blanched samples were used for experiment control. After the pretreatment, all samples were dried at 50 °C and analysed in terms of microstructure and elemental distribution using scanning electron machine. Results showed that fresh and blanched samples of fluted pumpkin leaf exhibited microstructural features that were clearly different from samples pretreated by magnetic field. Pretreated samples showed contents of: 1.3–4.35% sodium; 1.20–3.42% potassium; 1.19–6.10% calcium; 0–5.10% magnesium and 1.22–6.62% iron. Changes in microstructures of samples caused by magnetic field pretreatment led consequently to better retention/improvement in elemental distribution in contrast to blanched and fresh samples in majority of cases.